Memorando (2017)
MEMORANDO is an editorial piece that is intended to work as a reflection of the reader's memory. This book tries to create a journey through a person's memory in a timeless way, since his/her memory is one of a kind, and is up to the person to determine when did their memories happen.--Tomado del Formato de Documento de Grado.